Nghiên cứu ảnh hưởng của nồng độ chất hoạt động bề mặt CTAB đến cấu trúc vật liệu nanosilica - Phương, Hoàng Thị; Tiến, Hoàng Xuân; Ngọ, Đinh Thị (Vietnam Journal of Chemistry, 2016)
This paper covered a nanostructured silica preparation by condensation method, and effect of variation of CTAB concentration to structure and property of the as-synthesized nano-silica. The condensation was established in an alkaline environment caused by NH3 solution, and the precursor TEOS was used for the process. The condensation was carried out at ambient temperature for about 13 hours; then the precipitation was filtered, dried and calcined at 600 oC for 3 hours to obtain the final product. The nano-silica existed in amorphous phase with particle size ranging from 20 nm to 30 nm in ethanol solution with 8 % concentration of CTAB. The nano-silica could be used in various applications such as adsorption, support for catalysts, etc. because of its high surface area, fine and uniform particles. Some techniques were used such as XRD, SEM, TEM, EDX and BET for characterizing the obtained nano-silica. Keywords. Nano-silica, condensation, TEOS, nanomaterials.